The Search of Western Youth for Experience of the Divine through Indian Culture - Caroline Mackenzie (Journal of Dharma, 1987)
For many young people in the West today the Christian reI igion seems to be a closed book. Church-going or active belonging to a community is the exception rather than the rule for most of them. This alienation from traditional patterns of religion, should not however be interpreted as indicating an attitude of indifference to spirituality. It is more that their experience of meaning, which ultimately could also be called the divine does not coincide with what they find in their local church.